2016
DOI: 10.1111/jmi.12490
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of V2O5 thin film on conductive electrode

Abstract: Vanadium pentoxide V O thin films were grown at room temperature on ITO coated glass substrates by electrochemical deposition. The resulting films were annealed at 300, 400 and 500°C for 1 h in ambient environment. The effect of heat treatment on the films properties such as surface morphology, crystal structure, optical absorption and photoluminescence were investigated. The x-ray diffraction study showed that the films are well crystallized with temperatures. Strong reflection from plane (400) indicated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It is evident that a certain amount of I ions from the perovskite layer migrate toward the top electrode passing through porous PC 61 BM (ETL) by an internal electric field with a Cu electrode. [10,11,16,24] Hence, these ion migrations probably cause the deterioration of the interface (ETL/Cu) in the I-PSCs. In contrast, the sample with BTA-3 showed that a large amount of I ions were found in the position of the perovskite layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that a certain amount of I ions from the perovskite layer migrate toward the top electrode passing through porous PC 61 BM (ETL) by an internal electric field with a Cu electrode. [10,11,16,24] Hence, these ion migrations probably cause the deterioration of the interface (ETL/Cu) in the I-PSCs. In contrast, the sample with BTA-3 showed that a large amount of I ions were found in the position of the perovskite layer.…”
Section: Resultsmentioning
confidence: 99%
“…improved moisture stability of I-PSCs by inserting a dense and impermeable metal oxide layer, e.g., TiO 2 , AZO, V 2 O 5 , WO 3 , and MoO 3, between the ETL and top electrode. [13][14][15][16] However, because of the complicated and tedious methods involved, such as atomic layer deposition (ALD) and vacuum evaporation deposition, this system cannot be applied to the final goal of commercialization of PSCs, e.g., solution processable perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The structural analysis of ITO-coated V 2 O 5 thin films with two different molarities was carried out by XRD as shown in [25]. Other peaks are due to the ITO coated glass substrate.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Where R is the KM function (absolute diffuse reflectance), k is the absorption coefficient and s is the scattering coefficient. In DRS the absorption can be calculated from a plot [k/s*hν] 2 along y-axis and hν along the x-axis [19,20]. The bandgap of the material is obtained by extrapolating a straight line as shown in Fig.…”
Section: Bandgap and Thickness Measurementmentioning
confidence: 99%